Hardware Trojan Attacks: Threat Analysis and Countermeasures - Bhunia, Swarup; Hsiao, Michael S.; Banga, Mainak; Narasimhan, Seetharam (Proceedings of the IEEE, 2014)
Security of a computer system has been traditionally related to the security of the software or the information being processed. The underlying hardware used for information processing has been considered trusted. The emergence of hardware Trojan attacks violates this root of trust. These attacks, in the form of malicious modifications of electronic hardware at different stages of its life cycle, pose major security concerns in the electronics industry. An adversary can mount such an attack with an objective to cause operational failure or to leak secret information from inside a chip-e.g., the key in a cryptographic chip, during field operation. Global economic trend that encourages increased reliance on untrusted entities in the hardware design and fabrication process is rapidly enhancing the vulnerability to such attacks. In this paper, we analyze the threat of hardware Trojan attacks; present attack models, types, and scenarios; discuss different forms of protection approaches, both proactive and reactive; and describe emerging attack modes, defenses, and future research pathways.